Phytochemical evaluation and HPTLC fingerprint profile of various extracts of Cassia tora (Journal of Laboratory Animal Science, 2024)
The objective of the present study is to evaluate phytochemical composition and the high-performance thin layer  chromatography (HPTLC) fingerprint profile of methanol, ethanol, ethyl acetate, acetone, and aqueous extracts of  medicinally useful plant Cassia tora. The CAMAG HPTLC system was used for the fingerprint profiling of various  extracts of C. tora using the mobile phase toluene: ethyl acetate: glacial acetate (55: 45: 3 v/v/v). The profile showed  that the various extracts of C. tora exhibited several peaks with different Rf values when visualized at 254 nm and 366  nm. The results from HPTLC fingerprint scanned at wavelength 550 nm revealed the presence of 18, 13, 15, 12 and 14  phytoconstituents in methanol, ethanol, ethyl acetate, acetone, and aqueous extracts, respectively. The result of HPTLC  analysis of various extracts of C. tora shows that the maximum number of chemical constituents present in methanolic  extract in comparison to ethanol, ethyl acetate, acetone, and aqueous extracts of C. tora in given solvent system of toluene,  ethyl acetate and glacial acetate. Further bioactivity guided fractionation and analysis of isolated chemical entity can reveal  the active constituents in the various extracts of C. tora. Phytochemical analysis revealed the presence of carbohydrates,  proteins. glycosides, sapnonins, flavonoids, phenolics and tannins, phytosterols and triterpenoids.
Keywords: Cassia tora; Phytochemical analysis; HPTLC; Fingerprint.